The Impact of Subordinate2019;s Trust in Supervisor and Felt Trust on Subordinate Psychological Empowerment (Global Journal of Management and Business Research, 2019)
Em powering employees and building trust in close relationships become more vigorous consideration in the organization for surviving and competing in the business context The purpose of this study was to examine the impact of subordinate s trust in supervisor and felt trust on subordinate psychological empowerment To attain this research objective we collected data from 110 executive level employees who are working in a reputed garment manufacturing company in Sri Lanka We used survey method for data collection and used simple linear regression for data analysis The results of this study showed that the subordinate s trust in supervisor significantly influence on subordinate overall psychological empowerment Further the results showed that subordinate s felt trust has significant positive effect on subordinate overall psychological empowerment Based on these findings we recommend to the management ensure healthy relationships among supervisors and subordinates through effective communication and leadership practices in order to create a sense of empowerment within employees However this study based on executive level employees in one garment manufacturing company in Sri Lanka which hinder the generalizability of our findings
Keywords: trust; felt trust; trust in supervisor; and psychological empowerment